2007
DOI: 10.1097/ta.0b013e31802ce9bd
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cognitive, Emotional, and Functional Outcomes in Trauma Intensive Care Unit Survivors Without Intracranial Hemorrhage

Abstract: The majority of trauma survivors without intracranial hemorrhage display persistent cognitive impairment, which is nearly twice as likely in those with skull fractures or concussions. This cognitive impairment was associated with functional defects, poor quality of life, and an inability to return to work. Future research must delineate modifiable risk factors for these poor outcomes, especially in patients with skull fractures and concussions, to help improve long-term cognitive and functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 42 publications
3
57
1
Order By: Relevance
“…To date this has not been done and therefore there are no large-scale, long-term prospective studies of non-sports related concussion that have been conducted. However, the study by Jackson et al (2007) is a first attempt to accomplish such, where they examined their university-based Trauma I center registry for a single year and identified 97 adult trauma patient survivors from their ICU who had negative CT scan for intracranial hemorrhage, ostensibly eliminating those with obvious severe head injury. Within 12 to 24 months post-discharge, they were able to follow-up with a comprehensive neuropsychological battery of tests on 58 of these subjects and presence of concussion was associated with poorer neuropsychological outcome.…”
Section: Confounding Factors That Must Be Considered In the Design Ofmentioning
confidence: 99%
“…To date this has not been done and therefore there are no large-scale, long-term prospective studies of non-sports related concussion that have been conducted. However, the study by Jackson et al (2007) is a first attempt to accomplish such, where they examined their university-based Trauma I center registry for a single year and identified 97 adult trauma patient survivors from their ICU who had negative CT scan for intracranial hemorrhage, ostensibly eliminating those with obvious severe head injury. Within 12 to 24 months post-discharge, they were able to follow-up with a comprehensive neuropsychological battery of tests on 58 of these subjects and presence of concussion was associated with poorer neuropsychological outcome.…”
Section: Confounding Factors That Must Be Considered In the Design Ofmentioning
confidence: 99%
“…3,4,9 There have been various attempts to predict which individuals will recover rapidly from injury and, conversely, which individuals will continue to experience health status compromise on a medium or long-term basis. 3,5,17 However, little of this research has been based on a complex predictive model, which is likely to provide greater accuracy and explanatory ability.…”
Section: Introductionmentioning
confidence: 99%
“…1 The ongoing effects of injury have been shown to impact on all aspects of a person's life, 2 including compromised physical [3][4][5][6] and psychological functioning. 4,[6][7][8][9][10][11] The economic consequences of injury are also substantial. Rates of return to work following severe injury are variable, but approximately 50% of patients have not returned to work within five years.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In terms of co-occurrence of these conditions, the incidence rate of 19% in our study was similar to the range (11%-27%) of incidence of PTSD reported in civilian patients with mild to severe TBI from injuries such as motor vehicle crashes, falls, and assault. 19,22,[27][28][29] Our findings suggest that the brain responds similarly in both populations to a range of physical and emotional injuries that may be specific to military or civilian populations.…”
Section: Discussionmentioning
confidence: 84%